Analysis of heat stress in UK dairy cattle and impact on milk yields - Robert J H Dunn; Naomi E Mead; Kate M Willett; David E Parker (Environmental Research Letters, 2014)
Much as humans suffer from heat-stress during periods of high temperature and humidity, so do dairy cattle. Using a temperature-humidity index (THI), we investigate the effect of past heatwaves in the UK on heat-stress in dairy herds. Daily THI data derived from routine meteorological observations show that during the summer, there has been an average of typically 1 day per year per station over the past 40 years when the THI has exceeded the threshold for the onset of mild heat-stress in dairy cattle. However, during the heatwaves of 2003 and 2006, this threshold was exceeded on typically 5 days on average in the Midlands, south and east of England. Most dairy cattle are in the west and north of the country and so did not experience the severest heat. Milk yield data in the south-west of England show that a few herds experienced decreases in yields during 2003 and 2006. We used the 11-member regional climate model ensemble with the A1B scenario from UKCP09 to investigate the possible future change in days exceeding the THI threshold for the onset of mild heat-stress. The number of days where the THI exceeds this threshold could increase to over 20 days yr ^−1 in southern parts of England by the end of the century.